Examining Changes in Sleep Duration Associated with the Onset of the COVID-19 Pandemic: Who is Sleeping and Who is Not?. Issue 2 (3rd April 2023) - Batool-Anwar, Salma; Robbins, Rebecca; Ali, Shahmir H.; Capasso, Ariadna; Foreman, Joshua; Jones, Abbey M.; Tozan, Yesim; DiClemente, Ralph J.; Quan, Stuart F.
Abstract: The COVID-19 pandemic has resulted in social isolation and reports of insomnia. However, reports of changes in sleep duration and associated factors are few. To determine the impact of COVID-19 on changes in sleep behavior, data were analyzed from an online survey of adults recruited via social media that included questions asking whether the respondent slept less or more after the onset of the pandemic as well as self-reported sociodemographic and occupational information; beliefs about COVID-19; and responses pertaining to loneliness, anxiety, and depression. There were 5, 175 respondents; 53.9% had a change in sleep duration.17.1% slept less and 36.7% slept more. Sleeping more was related to greater education, being single/divorced/separated, unemployed or a student. Being retired, divorced/separated or a homemaker, and living in the Mountain or Central time zones were associated with less sleep. Beliefs that COVID-19 would result in personal adverse consequences was associated with both more and less sleep. However, the strongest associations for both more and less sleep were seen with depression, anxiety, and loneliness. In summary, changes in sleep duration since the start of the COVID-19 pandemic were highly prevalent among social media users and were associated with several sociodemographic factors and beliefs that COVID-19 would have adverse personal impacts. However, the strongest associations occurred with worse mental health suggesting that improvements may occur with better sleep. Supplemental data for this article is available online at https://doi.org/10.1080/08964289.2021.2002800 .